Estudos reológicos de cimentos asfálticos - Leite, Leni Figueiredo Mathias (1990)
This work proposes to establish rheological parameters for petroleum asphalt cements, representatives of their performance as paving material. An exhaustive survey of studies already done in this subject, was made in order to prepare a state-of-art about asphalt cement rheology and its correlation to chemical characterization and mechanical properties of bituminous mixtures. The experimental procedure included: rheological tests on asphalt cement samples using cone-plate viscometer and dynamic mechanical thermal analyser; comparison with properties of a standard sample, derived from Venezuelan crude; and correlation with mechanical properties. The weathering effect is compared to the ageing in-situ, through rheological determinations in samples taken from diferent pavement depths. The rheological behaviour was interpreted at the sight of molecular structure. The obtained results revealed that the selected rheological parameters (viscosity at 25 °c, at shear rate of 0,05 s-1, complex flux grade, temperature at which loss modulus is maximum) correlated well with mechanical properties. Increasing the viscosity, one observes greater resilient modulus, greater fatigue life at imposed stress and higher temperature which causes heat dissipation, reducing the tendency to permanent deformation. The rheological behaviour of the samples was non-Newtonian, pseudoplastic, a little bit thixotropic and presented transition correspondent to the molecular mobility as a whole at ambient temperature. This behaviour was interpreted as asphaltenes disagglomeration in function of shear stress or temperature increase. The agglomeration comes from heteroatoms content, compatibility between constituents, aromaticity and free volume. The ageing is rheologically regarded by increase of consistency and pseudoplasticity due to asphaltenes content increase. The carbonyl compounds and polyaromatics, formed by oxidation, reduced the intermolecular forces intensity, when shear stress are applied.